Let's get physical: Impacts of climate change physical risks on provincial employment - Thibaut Duprey; Soojin Jo; Geneviève Vallée (Bank of Canada, 2024)
We analyze 40 years' worth of natural disaster shocks in Canada, using a local projection framework to assess their impact on provincial labour markets. We find that disasters decrease hours worked within a week and lower wage growth in the medium run. The impact is driven by periods of employment slack, which suggests that disasters act as a catalyst for already weak local economies. We also find a more tempered response over time, possibly due to adaptation or stronger federal financial support. Finally, we document substantial heterogeneity across disaster types. Overall, our study highlights that natural disasters can detrimentally affect vulnerable workers through the income channel.
Keywords: C33; E24; J3; Q54; 330; Climate change; Regional economic developments; Labour markets